BETWEEN STIGMA AND SURVIVAL: LIFE NARRATIVES OF VIETNAMESE BRIDES IN CHINA - Pu, Weikang; Elfira, Mina (International Review of Humanities Studies, 2026)
The phenomenon of cross-border marriages between Vietnamese women and Chinese men is often reduced by mainstream media to simplified stereotypes—depicting them as victims of human trafficking, impoverished women seeking economic escape, or submissive "imported brides." Such depictions obscure the everyday realities through which these women confront and negotiate social stigma in a foreign socio-cultural environment. Drawing on narrative interviews with ten Vietnamese brides living in different regions of China, this study examines how stigma is experienced and negotiated through everyday survival strategies. Using a qualitative narrative approach, this research explores how participants respond to stigma through practices such as economic self-reliance, language acquisition, domestic labor, community-building, and selective identity performance. Rather than viewing identity as fixed, the findings suggest that hybrid or dual identities emerge through ongoing negotiations shaped by daily survival and social expectations. In this process, being “Chinese” in certain familial contexts while remaining “Vietnamese” within personal and community spaces becomes a practical way of maintaining dignity and stability.